Nature and the international: towards a materialist understanding of societal multiplicity. Issue 3 (2nd April 2020) - Corry, Olaf
ABSTRACT: The global environmental crisis requires a grasp of how human society interacts with nature, but also, simultaneously, how the world is divided into multiple societies. International Relations has a weak grasp of nature treating it as external to the international – an 'environment' to be managed – while environmentalism has a planetary epistemology that occludes the significance of the international. How to break this impasse? While neither Geopolitics nor 'new materialism' capture the complex conjuncture of socio-natural and inter-societal dynamics, I argue that Justin Rosenberg's theorization of the international as 'the consequences of societal multiplicity' provides a theoretical opening. If a materialist notion of societal is adopted, 'societal multiplicity' allows human-natural and international dynamics to be grasped together. Thus, climate change is not a problem arising exogenously to the international, but something emerging through international dynamics, reciprocally affecting the units, structure and processes of the international system itself.